Investigation of high capacity heat energy storage for building applications - Ding, Yate (2014)
The problems of excessive consumption of fossil resources, oil shortages and greenhouse gas emissions are becoming increasingly severe. Research and development work on new methods of thermal energy storage are imminently required. To effectively store seasonal renewable energy, a novel high capacity heat storage system has been designed and evaluated/validated through laboratory experiments and numerical simulations in this research. The system is driven by direct flow evacuated tube solar collector with enhanced PCM tank and intends to be applied in residential and commercial buildings.